THE INFLUENCE OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE PERUMDA TIRTA MANGKALUKU PALOPO CITY - Prestiawan, Wisnu Ainun; Sampetan, Suparni; Hasbi, Andi Rizkiyah (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aimed to evaluate the influence of income and work motivation on employee performance. The study was conducted on a group of 60 permanent employees from Perumda Tirta Mangkaluku Palopo. A sample size of 52 individuals was chosen for this investigation. This study employed a questionnaire as a tool for gathering data. This study employed validity and reliability assessments to evaluate the correctness and consistency of the data, and utilized T and F tests to examine the hypothesis. This study demonstrates the absence of a correlation between employee remuneration and the performance of Perumda Tirta Mangkaluku Palopo. Nevertheless, this study demonstrates a correlation between remuneration and job motivation, which subsequently impacts the performance of employees at Perumda Tirta Mangkaluku Palopo. Both elements exert a substantial influence on the performance of employees within the firm